2018
DOI: 10.3390/w10040436
|View full text |Cite
|
Sign up to set email alerts
|

An Increase of Abundance and Transcriptional Activity for Acinetobacter junii Post Wastewater Treatment

Abstract: A membrane bioreactor (MBR)-based wastewater treatment plant (WWTP) in Saudi Arabia is assessed over a five-month period in 2015 and once in 2017 for bacterial diversity and transcriptional activity using metagenomics, metatranscriptomics and real time quantitative polymerase chain reaction (RT-qPCR). Acinetobacter spp. are shown to be enriched in the chlorinated effluent. Members of the Acinetobacter genus are the most abundant in the effluent and chlorinated effluent. At the species level, Acinetobacter juni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 78 publications
(104 reference statements)
0
9
0
Order By: Relevance
“…This special issue comprises of 11 research articles that fall within the scope of AMR. Broadly, topics extend from AMR monitoring and surveillance in environmental resources and effluents from water/wastewater treatment plants [32][33][34][35][36][37][38][39], antimicrobial ecological risk assessments of two river reservoir systems in China that are sources of drinking water supply [40,41], and exploring novel strategies of using engineered antimicrobial peptides (AMP) to target specific bacteria to disrupt biofilms that are major causes of chronic and persistent infections [42].…”
Section: Key Outcomes Of This Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…This special issue comprises of 11 research articles that fall within the scope of AMR. Broadly, topics extend from AMR monitoring and surveillance in environmental resources and effluents from water/wastewater treatment plants [32][33][34][35][36][37][38][39], antimicrobial ecological risk assessments of two river reservoir systems in China that are sources of drinking water supply [40,41], and exploring novel strategies of using engineered antimicrobial peptides (AMP) to target specific bacteria to disrupt biofilms that are major causes of chronic and persistent infections [42].…”
Section: Key Outcomes Of This Special Issuementioning
confidence: 99%
“…Jumat et al [37] conducted an ESBL study of diversity and transcriptional activity of bacteria in a WWTP in Saudi Arabia using metagenomics, metatranscriptomics and real-time qPCR. They found an increase in the relative abundance of Acinetobacter junii in MBR-and chlorinated treated effluent.…”
Section: Amr Monitoring and Surveillancementioning
confidence: 99%
“…In addition, it was shown that certain bacteria, such as Acinetobacter spp. are strongly resistant to chemical disinfectants (14).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of emerging contaminants (ECs) such as pharmaceuticals, illicit drugs, personal care products, antibiotic-resistant pathogens and antibiotic resistance genes in untreated wastewaters have been widely reported by many studies [1][2][3][4] . Heavy metals in influent of wastewater treatment plant located in Thuwal, Saudi Arabia was measured, and the result revealed heavy metal concentration to range from several ppb to more than 20000 ppb in the untreated wastewater 5 . Many of these ECs can detrimentally impact the natural ecosystems if left unremoved from the wastewaters.…”
Section: Introductionmentioning
confidence: 99%